2004
DOI: 10.1039/b309160k
|View full text |Cite
|
Sign up to set email alerts
|

Transferrin binding and transferrin-mediated cellular uptake of the ruthenium coordination compound KP1019, studied by means of AAS, ESI-MS and CD spectroscopy

Abstract: Indazolium trans-[tetrachlorobis(1H-indazole)ruthenate(III)] (KP1019) shows particular promise as an antitumour agent against colorectal cancer. It is known that KP1019 reacts with human serum proteins, whereby the major amount binds to albumin (present in large excess) and a smaller amount to transferrin. It has been hypothesised that transferrin-mediated uptake by transferrin receptor expressing tumour cells may in part explain the apparent tumour selectivity of this compound. Circular dichroism spectroscopy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
186
2
5

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 198 publications
(198 citation statements)
references
References 28 publications
5
186
2
5
Order By: Relevance
“…1) which showed promise in a clinical phase I trial in terms of activity but also low toxicity [38][39][40]. The latter properties are thought to be related to its selective mode of action comprising the transport into the tumor via the Tf cycle and the reduction in the tumoral tissue [19,41,42]. Recent studies on the binding to plasma proteins showed a kinetic preference for the binding to Tf but higher binding constants for albumin, both being important transport proteins for drugs [10,11,31].…”
Section: Resultsmentioning
confidence: 99%
“…1) which showed promise in a clinical phase I trial in terms of activity but also low toxicity [38][39][40]. The latter properties are thought to be related to its selective mode of action comprising the transport into the tumor via the Tf cycle and the reduction in the tumoral tissue [19,41,42]. Recent studies on the binding to plasma proteins showed a kinetic preference for the binding to Tf but higher binding constants for albumin, both being important transport proteins for drugs [10,11,31].…”
Section: Resultsmentioning
confidence: 99%
“…46 Interestingly, the results found for these three metallaprisms are in contrast to those observed with other ruthenium complexes. For instance, KP1019 was shown to bind to apoTf as evidenced by ESI-mass and CD spectra, 47 and RAPTA-C was shown to bind to Ub and metallothionein-2. 48 All NMR and MS experiments strongly suggest that no covalent binding takes place between the metallaprisms and the five selected proteins.…”
Section: Nmr and Ms Investigations Of The Interaction Between Metallamentioning
confidence: 99%
“…The 3-(4,5-dimethyl-2-thiazoyl)-2,5-diphenyltetrazolium bromide cell survival test was performed 24 h after the irradiation. The LD 50 values (light dose necessary to inhibit 50% cell survival) were determined using the medium effect algorithm [27] that the complexes are taken up by HeLa, Ovcar, and A2780 cells and concentrate in the cell cytoplasm and organelles, but not in the nucleus, as did our previously reported compounds [19,20] but this contrasts with some ruthenium-based drugs known to accumulate in the nucleus [33,34]. Photodynamic studies provided coherent results compared with uptake studies since our complexes induce phototoxicities in HeLa cervix and A2780 ovary carcinoma cell lines and not in other cancer and normal fibroblast cells.…”
Section: Discussionmentioning
confidence: 99%